Integralni opis svetil in svetlobnih virov - Malovrh Rebec, Katja (Gradbeni vestnik, 2015)
Holistic evaluation of lamps and light sources should include the lighting engineering parameters, as well as parameters evaluating photobiological effects and environmental impacts. Photobiological effects are currently the target of many research efforts, based on which recently some parameters for their evaluation have been suggested. Moreover, in the field of the environment and the sustainability of the use of lamps and resources constant progress is present. The Environmental Product Declaration (EPD), which describes the environmental impacts of products, is intended mainly to the business-to-business (B2B) communication. It complies with ISO 14025 standard.But merely energy consumption during the use of a product is not sufficient for environmentally aware investors. They and their customers want to know how much energy is built into the product in the production phase and what happens when the product is discarded. The EPD declaration is based on anassessment of the full life-cycle or LCA (Life Cycle Assessment). We have prepared a detailed analysis and interpretation of 5 cases of lamps' EPSs of different manufacturers. In some lamps there are LED sources installed (Philips, Zumtobel) in others compact fluorescent lamps (Thorn) or metal halide sources (We-Ef Leuchten); there is also an example of ballast (Tridonic). A major challenge remains the comparability of results.
Keywords: okoljske zahteve; svetila; svetlobna tehnika; tehnične zahteve